Figure. Image and democratic perversion in Deleuze’s thought - Nóbrega, Diogo (Scenari, 2024)
plex account of the concept of Figure in Francis Bacon: Logique de la Sensation and in Cinéma 1: L’image-mouvement. In the first part, I show that Deleuze’s theoretical work on the Figure implies an extensive discussion of the Greek vocabulary of the image. The Figure, he argues, is “an Image, an Icon”, that is, not an εἴδωλον but an εἰκών, not the reproduction of an ideal visuality but the rendering visible of forces that are not themselves visible, not a matter of producing a lifeless body, a corpse, as in Plato’s account of the image, but of a body without organs, which serves as a model for a different death, an impersonal death inscribed in the time of Αἰών, in implicating the possibility of having been repeated and of being repeated to infinity, all in liberating intensive differences on each occasion. In the second part, I argue that this internalization of death in and as Figure, involving an ever-returning event of transformation, entails a complete rethinking of mimesis, that is, no longer the production of resemblance, the transcendental imposition of form and stability, but the doubling of transformation, of aionic time itself. Deleuze calls this mimetic commitment to transformation “perversion”. I conclude by focusing on the political implications of this perversion, arguing that it informs Deleuze’s account of democracy as becoming-democratic, taking on an idea already at work in Aristotle’s Politics.